Analisis SWOT terhadap Strategi Penjualan Smartphone Xiaomi dan Vivo - Eriana Afnan; Sam'un Jaja Raharja (Universitas Winaya Mukti, 2020)
The growth of smartphone users every year continues to grow and is a necessity for its users. Every smartphone company competes for generous consumers and competes to provide the technology and features needed by its users. This research was conducted to see a SWOT analysis of sales strategies on Xiaomi smartphones and Vivo smartphones in terms of differentiation strategy, focus strategy, cost leadership strategy. This study uses a digital use database to find articles relevant to the SWOT analysis of sales strategies on Xiaomi smartphones and Vivo smartphones. This type of research used in this research is descriptive analysis with a qualitative approach. The analysis method used is the SWOT analysis and Porter's Generic Strategy. The results showed that in total, this smartphone company had implemented the generic porter strategy well. However, the Vivo company's focus strategy is only applied so that the Vivo company can focus on marketing efforts on one or two market segments and create a marketing mix that is specific to that market so that the company can find better market needs.